Biosynthesis of poly(ethylene glycol)-supported palladium nanoparticles using Colocasia esculenta leaf extract and their catalytic activity for Suzuki–Miyaura cross-coupling reactions1. Issue 89 (27th September 2015) - Borah, Raju Kumar; Saikia, Hirak Jyoti; Mahanta, Abhijit; Das, Vijay Kumar; Bora, Utpal; Thakur, Ashim Jyoti
<x xml:space="preserve">Abstract</x> A green and efficient method for the synthesis of PEG supported Pd-NPs has been developed using aqueous extract of C. esculanta leaf. The prepared NPs show excellent catalytic activity for Suzuki–Miyaura cross-coupling reaction at room temperature.